Seismic hazard in Malaysia / Shuhaidar Annuar (Faculty of Civil Engineering, 1992)
Malaysia is not a very seismic country. Nevertheless its state of Sabah is faced with potential hazard from medium size earthquakes of local origin and also the westcoast states in the Peninsula Malaysia are treathened by possible amplification of ground motion originating from not-too distant large earthquakes over Sumatra (Indonesia). Evaluating seismic hazard in Malaysia is a difficult task. Data recorded instrumentally began in 1976, using seismograph. There's also low frequency of occurrence and lack of understanding of the origin of these local earthquakes .However protection from earthquake effects cannot be neglected. The above mentioned areas of seismic hazard were looked into using the Gutenberg-Richter Relation (GRR) and the Extreme Value Distribution (EVD) baesd on the 15-years data available (1976 - 1990) . (Ref.1) Over Sabah GRR was applied and Kaila and Narain's (Ref.l) method was used to obtain the values of a and b and then the return periods for different earthquake magnitude. For not-too-distant earthquakes affecting the Peninsula Malaysia, Penang Island was selected as the site and all the earthquakes occuring within 450 km radius were taken into consideration to calculate the return periods of different magnitudes. Both the GRR and EVD were used.